Protocol power: Matter, IoT interoperability, and a critique of industry self-regulation - Colin Crawford (Internet Policy Review, 2024)
This article puts forth the concept of protocol power as the disproportionate influence of dominant platform actors to shape and set industry-wide standards, and thus determine certain rules of inclusion at the technical, existential level of protocol. In this way, protocol power shapes and prefigures dynamics of platform power and intermediation as ever more objects are made "smart" and connected through such standards. To examine protocol power, I take up the case of Matter, an emerging Internet of Things connectivity standard led by Big American Tech promising to make all smart things interoperable across all platform ecosystems in the face of growing critiques from regulators, developers, and users. Increased levels of interoperability and connectivity are opening up new sites of data production and accumulation, and provide more opportunities for service and subscription provision by dominant platforms. This article argues that Matter and its promises exemplify processes of industry self-regulation, networked governance, and power-sharing among dominant actors in the tech industry in efforts to maintain and expand their market and platform power.
Keywords: 300; Interoperability; Protocols; Internet of things; Self-regulation; Matter